2017
DOI: 10.1103/physrevb.95.020415
|View full text |Cite
|
Sign up to set email alerts
|

Double vibronic process in the quantum spin ice candidate Tb2Ti2O7 revealed by terahertz spectroscopy

Abstract: The origin of quantum fluctuations responsible for the spin liquid state in Tb2Ti2O7 has remained a long standing problem. By synchrotron-based terahertz measurements, we show evidence of strong coupling between the magnetic and lattice degrees of freedom that provides a path to the quantum melting process. As revealed by hybrid crystal electric field-phonon excitations that appear at 0.67 THz below 200 K, and around 0.42 THz below 50 K, the double vibronic process is unique for Tb 3+ in the titanate family du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
(54 reference statements)
4
27
0
Order By: Relevance
“…In recent terahertz spectroscopy measurements [83], four peaks were found in the THz spectrum: P0 (hω P0 = 1.37 meV), P1 (hω P1 = 1.71 meV), P2 (hω P2 = 2.08 meV), and P3 (hω P3 = 2.78 meV). The energies and temperature dependence of P0 and P2 suggests they are excitations between the members of the ground-state and CEF1 doublets, with equal splitting of each doublet due to magnetoelastic coupling.…”
Section: B Comparison With Terahertz Spectroscopy Experimentsmentioning
confidence: 96%
See 1 more Smart Citation
“…In recent terahertz spectroscopy measurements [83], four peaks were found in the THz spectrum: P0 (hω P0 = 1.37 meV), P1 (hω P1 = 1.71 meV), P2 (hω P2 = 2.08 meV), and P3 (hω P3 = 2.78 meV). The energies and temperature dependence of P0 and P2 suggests they are excitations between the members of the ground-state and CEF1 doublets, with equal splitting of each doublet due to magnetoelastic coupling.…”
Section: B Comparison With Terahertz Spectroscopy Experimentsmentioning
confidence: 96%
“…However, our observation of an overall exciton dispersion closely similar to that discussed by Kao et al [42] suggests that ignoring the admixture of excited states will ultimately be unrealistic. Furthermore, given the numerous couplings between phonons now catalogued in Tb 2 Ti 2 O 7 [CEF1 and TAP to produce the MEM discussed here, CEF1 and an overlying optical mode to give a magnetoelastic optical mode (MEOM [16]) observed by a terahertz spectroscopy experiment mentioned further below [83], CEF3 and an optical phonon to produce a MEOM as described in Ref. [16])], the importance of effective coupling of multipoles by phonons [84] should also be assessed.…”
Section: A Overall Structure Of Crystal Field and Magnetoelastic Excmentioning
confidence: 98%
“…Using high-resolution synchrotron-based terahertz spectroscopy, we have probed the lowest energy excitations of Tb2Ti2O7 (see Figure 1). It is revealed that a double hybridization of crystal-fieldphonon modes is present across a broad temperature range from 200 k down to 6 K [1]. This so called vibronic process affects the electronic ground state that can no longer be described solely by electronic wave functions.…”
Section: Published: 5 September 2019mentioning
confidence: 99%
“…[259][260][261][262][263][264] Due to statistical identity of ground state manifolds of these materials and entropy of ice, these were termed as spin ice materials which possess 2-in 2-out spin configuration on each tetrahedron. [259][260][261][262][263][264] Due to statistical identity of ground state manifolds of these materials and entropy of ice, these were termed as spin ice materials which possess 2-in 2-out spin configuration on each tetrahedron.…”
Section: Magnetic Monopole Dynamics In Pyrochlore Titanates Using Thzmentioning
confidence: 99%